High‐impact wet‐milling: Effects of steeping conditions on rice starch attributes. (30th June 2016) - Loubes, Maria Ana; Barrera, Gabriela Noel; Tolaba, Marcela Patricia
Abstract : Planetary ball wet‐milling of rice was evaluated in comparison with traditional wet‐milling. The effect of alkali and surfactant concentrations on starch recovery and purity, crystallinity loss, pasting profile, and gel stability were investigated based on the Doehlert design. Particle size, crystallinity degree, and water absorption capacity were not affected by steeping conditions although they differ from those of native starch due to the thermo‐mechanical damage associated to high‐impact milling. Ball wet‐milling allows significant reductions of alkali level and steeping time (from 24 to 1 h) and a high‐quality starch is produced due to "in situ" steeping during ball milling. From the response surface method was found that combinations of alkali–surfactant affected the pasting properties and syneresis of starch. Isolated starches presented an advance in peak time and higher values of peak viscosity, breakdown, and initial pasting temperature in comparison with control. A wide range of peak viscosity (4360–7030 cP) could be obtained by selecting a convenient steeping condition. The freeze–thaw stability of starch gels was dependent of surfactant level. These results can be used to improve the manufacture and the selection criteria of rice starch with desirable properties.